Reanalysis of “Raptorex kriegsteini”: A Juvenile Tyrannosaurid Dinosaur from Mongolia - Fowler, Denver W.; Woodward, Holly N.; Freedman, Elizabeth A.; Larson, Peter L.; Horner, John R. (PLOS ONE, 2011)
The carnivorous Tyrannosauridae are among the most iconic dinosaurs: typified by large body size, tiny forelimbs, and massive robust skulls with laterally thickened teeth. The recently described small-bodied tyrannosaurid Raptorex kreigsteini is exceptional as its discovery proposes that many of the distinctive anatomical traits of derived tyrannosaurids were acquired in the Early Cretaceous, before the evolution of large body size. This inference depends on two core interpretations: that the holotype (LH PV18) derives from the Lower Cretaceous of China, and that despite its small size, it is a subadult or young adult. Here we show that the published data is equivocal regarding stratigraphic position and that ontogenetic reanalysis shows there is no reason to conclude that LH PV18 has reached this level of maturity. The probable juvenile status of LH PV18 makes its use as a holotype unreliable, since diagnostic features of Raptorex may be symptomatic of its immature status, rather than its actual phylogenetic position. These findings are consistent with the original sale description of LH PV18 as a juvenile Tarbosaurus from the Upper Cretaceous of Mongolia. Consequently, we suggest that there is currently no evidence to support the conclusion that tyrannosaurid skeletal design first evolved in the Early Cretaceous at small body size.